Acute Fatty Liver Disease of Pregnancy in the Second Trimester - Faraz Afridi; Michael Feely; Raju Reddy (Case Reports in Critical Care)
Acute fatty liver of pregnancy (AFLP) is a rare disorder that typically presents in the third trimester. We report a case of a 21-year-old woman with a history of intrauterine fetal demise at 19 weeks’ gestation who developed fulminant liver failure 1 week after the fetal demise. She was diagnosed with AFLP as per the Swansea criteria. An orthotopic liver transplant was attempted but was unsuccessful. AFLP usually presents between the 30th to 38th weeks of gestation. However, it can occur in the postpartum period after only 19 weeks of gestation as highlighted in our case.